Mortality Rate of Cancer in Patients attending Mayo Hospital Lahore, Pakistan - Amjad, Sana; Saleem, Mehwish; Ashraf, Asfa; Iqbal, Muhammad Naeem (PSM Microbiology, 2020)
This retrospective study was conducted to determine the mortality rate of cancer in patients attending Mayo Hospital Lahore, Pakistan. The data was obtained from the medical record of the hospital for a period of 2 years that is from 2016 to 2017. All data were collected using standardized data collection Performa and analyzed by using SPSS-20. During the study period, a total of 3610 patients were registered in the hospital. One thousand seven hundred and fifty-seven (48%) were male while one thousand eight hundred and fifty-three (52%) were female. The mortality rate of cancer was high, a total of 206 patients expired at the hospital while most of the patients leave the hospital at the most serious stage of the disease. The mortality rate of cancer was slightly higher in males as compared to females, there were 111 (53.88%) males and 95 (46.11%) females out of 206 patients who were expired as a result of cancer. The highest mortality rate was observed in the patients with breast cancer (15%) followed by blood cancer (10.6%), lymphoma (9.7%), the cancer of oral cavity (7.76%), liver cancer (6.31%), lung cancer (6.31%), bone cancer (5.82%), ovarian cancer (4.36%), and tongue cancer (4.36%), of total cancer mortalities in last two years. The delay in diagnosis associated with high-stage cancer can result in a higher mortality rate. The study concluded that the incidence rate of breast cancer was highest among all cancer types during the study period. Further investigation should be done to determine the cause of cancer deaths so that better prevention should be done to reduce the mortality rate.